Comparing wavelengths simulated by the coastal wave model CWAM and TerraSAR-X satellite data - Gebhardt, Claus; Pleskachevsky, Andrey; Rosenthal, Wolfgang; Lehner, Susanne; Hoffmann, Peter; Kieser, Jens; Bruns, Thomas (Ocean Modelling, 2016)
The accuracy of the high resolution coastal wave forecast model CWAM is validated on the basis of sea state information from satellite images of TerraSAR-X (TS-X). At the same time, the performance of the satellite retrieval of sea state parameters is demonstrated. Employing 2-dimensional spatial Fourier Transformation, image spectra are derived from TS-X and locally varying patterns of the peak wavelength are provided using state-of-the-art satellite retrieval. Subsequently, wavelength comparisons are performed between a typical set of TS-X scenes acquired in December 2013 over the German Bight and the model hindcasts. The results are mostly in reasonable agreement. Potential shortcomings of the wave model are discussed as well.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Coastal wave model CWAM; Sea state analysis; Synthetic aperture radar (SAR); TerraSAR-X